LINKS BETWEEN LEARNERS MINDSET AND LANGUAGE LEARNING AUTONOMOUS LANGUAGE LEARNING HISTORY (LLH) - Ariani, Nina; Sahid, Abdul (Elite : English and Literature Journal, 2016)
Abstract Learning autonomy is one of the important factors that can help the learners to meet the learning goal. However, some learners are not enthusiastic to learn autonomously, they always need a teacher to help them. They sometimes just learn when the teacher asked them to do during the learning process, when they find some difficulties; they just give up and feel less confidence to solve it. This negative aptitude is caused by the students’ mindset in language learning. According to Carol Dweeck, fixed mindset students believe their basic abilities, their intelligence, their talents, are just fixed trait while growth mindset students understand that their talents and abilities can be developed through effort, good teaching and persistence. It indicates that, the fixed mindset learners seemingly have a problem with their mindset which leads them to be less motivated in language learning. Abstrak Hubungan antara Pola Pikir Pembelajar dan Pembelajaran Bahasa secara Autonomi (LLH). Belajar otonomi adalah salah satu faktor penting yang dapat membantu para peserta didik untuk memenuhi tujuan pembelajaran. Namun, beberapa peserta didik tidak bersemangat untuk belajar secara otonom, mereka selalu membutuhkan guru untuk membantu mereka. Mereka kadang-kadang hanya belajar ketika guru meminta mereka untuk melakukan selama proses pembelajaran, ketika mereka menemukan beberapa kesulitan; mereka hanya menyerah dan merasa kurang percaya diri untuk menyelesaikannya. Bakat negatif ini disebabkan oleh pola pikir siswa dalam belajar bahasa. Menurut Carol Dweeck, tetap pola pikir siswa percaya kemampuan dasar, kecerdasan mereka, bakat mereka, hanya tetap sifat sementara pertumbuhan pola pikir siswa memahami bahwa bakat dan kemampuan dapat dikembangkan melalui usaha, pengajaran yang baik dan ketekunan. Ini menunjukkan bahwa, peserta didik pola pikir tetap tampaknya memiliki masalah dengan pola-pikir mereka yang membawa mereka menjadi kurang termotivasi dalam belajar bahasa.